Risk factors in patients having renal stones in Al-Sader Teaching Hospital in Misan province - Zamil, ali Laibi (Karbala Journal of Medicine, 2019)
Introduction: Renal stone is one of the commonest renal conditions in Iraq and number of the patients who are suffering from this condition is one of the largest attendance to the In and Outpatient clinics. There are many risk factors leading to this condition and in this study trying to recognize the most common risk factors and compare with other studies. Patients and method: 67 cases were been chosen for this prospective study collected from admitted cases and Outpatient clinic in the main hospital in the province and the data were collected directly from the patients themselves and their medical records to identify the main risk factors causing their problems. The results: In this study many tables were getting for the main risk factors but try to concentrate about the commonest risk factors that discovered during the study and also to compare it with other studies in the same topic. Discussion: Making a comparison between this study and other studies were done in USA and UK, it has been found that the main risk factors for renal stones formation in western countries is the supplemental calcium and chronic or recurrent UTI and the gender factors are similar to this study. Conclusion: This study shows the most common risk factor for renal stone formation is chronic UTI then history of previous stone and the family history of renal calculi and effect of climate. Also increase incidence of renal stones in female more than male. The study also shows the living in urban area is more risk for renal stone formation than rural area.